An assault on poverty : basic human needs, science and technology (International Development Research Centre ; United Nations Conference on Trade and Development, 1997)
In An Assault on Poverty, the Panel on Technology for Basic Needs of the United Nations Commission on Science and Technology for Development offers analyses of poverty eradication and the role of science and technology with respect to sustainable human development, technical and vocational education, health, and small-scale economic activities, among other issues.